Domestic Private Sector Participation in Water and Sanitation : The Niger Case Study - Adamou Maiga, Taibou (World Bank, Niamey, 2016)
This report, developed for policy makers and sector development partners, highlights the manner in which the domestic private sector is successfully participating in the delivery of water and sanitation services in Niger. It outlines the factors for success as well as the challenges that need to be addressed to harness private sector resources and motivation for improved and sustainable services.There is a need to further strengthen the capacities of various rural water supply stakeholders, particularly communes, which contract and supervise the work of the operators. The capacities of operators and users’ associations also need to be developed to pursue ensure the operational sustainability of the systems.The technical assistance (TA) described in this Note has, over the past five years, supported the sector’s stakeholders’ efforts to work in synergy to foster the participation of domestic private entities in the management of rural water supply systems (RWSSs).The purpose of the TA hasbeen to ensure improved operational policy applicationof the PPP frameworks in the context of water supplyand urban sanitation in rural and small towns , which hasnot evolved much over time in relation to urban waterservices. The TA program consisted of training activities,market assessments, and options development studiesto inform decision-making and consensus-building ofdifferent stakeholders on resolving some challenges facingthese subsectors.Opportunities exist for the Government to promote the emerging domestic private operators with a view to raising their level of professionalism for better service delivery.